Barriers to Integrating Antiretroviral Therapy Services Into Community Health Centre: A Qualitative Study in Badung Regency - Made Sugiana; I Nyoman Sutarsa; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2015)
Background and purpose: Increasing of HIV+ cases resulted in the increasing demand for antiretroviral (ARV) and access to ART services. This study aims to explore barriers of integrating ART services into primary health centres in Badung District. Methods: Explorative interviews were conducted with CST officers at Badung District Hospital, puskesmas (health centres), NGOs, policy makers, community leaders and PLWHA. Data were collected by conducting indepth interviews, focus group discussion and observation. Data were thematically analysed. Results: The study found that there were variations in internal barriers across different puskesmas in Badung District to be a satellite site. The main internal barriers perceived by health officers particularly in relation to issues around the availability of human resources, lack of competencies and increase of workload. Internal capacity of puskesmas which also perceived as barriers including the availability of laboratory facilities, absent of operational procedures, limited information system and source of funds that predominantly still from donor agencies. External barriers perceived by respondent were stigma and discrimination. Conclusions: Barriers to integrate ART services into puskesmas consist of structural barriers from internal puskesmas as well as external barriers such as stigma and discrimination towards PLWHA.